Corporate Adjustments and Import Competition in the U.S. Apparel Industry - de la Torre, José; Arpan, Jeffrey S.; Jedel, Michael Jay; Ogram, Ernest W.; Toyne, Brian (Journal of International Business Studies, 1977)
This article examines the historical strategic adjustment process of ten apparel manufacturers as they reacted to high levels of import competition. The companies were divided into three groups according to their relative success and a series of propositions are offered linking adjustment strategies to performance. The article concludes by offering a series of public policy recommendations aimed at improving adjustment assistance to U.S. firms facing similar competitive pressures in the future.